STRATEGI KEPALA SEKOLAH DALAM MENJAMIN KUALITAS PROSES PEMBELAJARAN - Ulya, Lulu Khanifatul; Mahmudah, Fitri Nur (Idaarah: Jurnal Manajemen Pendidikan, 2023)
Learning is the main activity that occurs in the education unit; quality learning will have an impact on student learning outcomes and school output. This study aims to analyze and reveal the principal's strategy for ensuring a quality learning process. This research method uses descriptive qualitative research with a case study research design. As well as data collection techniques by observation and interviews based on observation and interview guidelines. The results that the researchers found in this study were: As for the several efforts made by the principal, namely guaranteeing teacher careers in the teacher mobilization program, supervising, and providing evaluations in the form of suggestions and input. Meanwhile, the teacher plays a role in determining learning strategies, managing classes, designing teaching modules, determining learning media that are in accordance with the characteristics of students, and establishing good relations with students and their parents. Assuring the quality of the learning process is not necessarily the responsibility of the principal, but it is part of the main task of a teacher in carrying out learning in the classroom.